Adaptation of shell morphology to different tidal zones—insights into phenotypic plasticity of Littorina brevicula - Lai, Siqi; Shi, Ling; Han, Yida; Tian, Ying; Hao, Zhenlin (Frontiers in Ecology and Evolution, 2025)
IntroductionThe adaptability of intertidal gastropods to their environmental niches is a critical aspect of their survival. Littorina brevicula, a common intertidal snail, exhibits phenotypic plasticity in response to varying tidal conditions. This study investigates the phenotypic plasticity and shell structure of L. brevicula across two disparate tidal zones to understand how these factors influence shell morphology and growth.MethodsA total of 254 specimens of L. brevicula were collected from the intertidal expanse. The analytical approach was tripartite, including traditional morphometric techniques, geometric morphometric methods (GM), and three-dimensional (3D) model simulation analyses. This comprehensive methodology allowed for a detailed examination of shell morphology and growth patterns.ResultsThe results demonstrated that shell growth in the high tidal zone was slower compared to the mid tidal zone. Morphological disparities were evident, with high tidal zone specimens showing lower spires and a more spherical shell conformation, while mid tidal zone specimens had elongated spires and a tower-like shell shape. 3D model simulation analyses revealed different stress distributions; the mid-tide zone simulation showed concentrated stress in a circumscribed region, whereas the high-tide zone simulation showed a more expansive stress distribution across the entire shell.DiscussionThe distinct morphological adaptations observed in L. brevicula across tidal zones suggest a strong influence of environmental factors on shell morphology. The slower growth and different stress distribution patterns in the high tidal zone may be indicative of the snails' response to more challenging environmental conditions. These findings provide essential evidence for understanding the adaptability of intertidal gastropods to their environmental niches.